External Debt and Economic Growth in Central Africa: Does the Profile of the Leader Matter? - Nelson Derrick Nguepi; Ibrahim Ngouhouo (International Journal of Empirical Economics)
This study highlights the role of political leadership in external debt management by translating its effectiveness into economic growth. We use data from World Development Indicators (2018), Archigos (version 4.1) for Goemans et al. (2009) and Scartascini et al. (2021) from 1975 to 2019. The estimation using the Driscoll–Kraay method gives us three good results: First, the analysis shows that external debt significantly slows growth in Central Africa. Second, there is a positive relationship between the age of political leaders and economic growth, as well as between the level of education of political leaders and economic growth. This means that there is a minimum age for good external debt management by political development leaders, just as there is a minimum level of education for political development leaders that increases the effectiveness of debt management external debt and thus promotes economic growth. On the other hand, this study concludes that the place of education of political leaders has a significant impact on debt management. African leaders educated in Africa manage external debt effectively, while African leaders educated in the West manage it poorly. As a result, the populations of Central African countries are encouraged to elect politicians who have studied in Africa.